Constable Receives 2013 William Gilbert Award: Response. Issue 28 (15th July 2014) - Constable, Catherine
<x xml:space="preserve">Abstract</x> Thank you for the generous citation. I am truly honored that the GP section considers me a worthy recipient of this award. As you might guess, I don't deserve exclusive credit for everything in Rick's citation, and if you look at the coauthors on all my publications, you can get a pretty good idea of who really did the work. I have been fortunate to work in a highly collegial environment at the University of California, San Diego, where my mentors, colleagues, postdocs, and students at Scripps Institution of Oceanography's Institute of Geophysics of Planetary Physics have been tremendously important to me. Additionally, this year (2013) marks 30 years since I first attended the AGU Fall Meeting, and the GP section has really been my scientific home within this organization, connecting me to a broader range of collaborators from all over the world. I owe thanks to a large number of people who have contributed to the fun of doing science and provided opportunities to discuss things in a highly collegial environment.